Implementation of C4.5 Method to Determine the Factor of Being Late for Coming to School - Cendana Puspitasari (Jurnal Riset Informatika, 2020)
Being late to school is a deviant act that violates the rules or regulations in the school, both written and unwritten. The discipline of students coming to school is the first to see. Some common factors that cause delays include distance to school, wake-up, departure hours, travel conditions, and vehicles used. In this study, the authors used the Classification algorithm with the C4.5 and Forward selection methods. The sample used was questionnaire data for class VIII (eight) State Junior High School students 271, totaling 270 students. Using training data, certain attributes are determined to form a classifier model. The results of this study are the results of the accuracy of the C4.5 method of 60.74%, with the results of the tree showing congestion is a factor of school delay and the results of the accuracy of 65.93% for Forward selection and the three best attributes.